Mycoflora associated with Basella spp. and their pathogenic potentiality - Akter, Sufia; Shamsi, Shamim (Bangladesh Journal of Scientific Research, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20235 Bangladesh J. Sci. Res. 26(1-2): 83-87, December-2013